Exploring the asymmetric effect of lending rate on economic growth in Ghana: Evidence from nonlinear autoregressive distributed lag model - Opoku Adabor (Cogent Business & Management, 2022)
While several studies have investigated the linear effect of lending rate on economic growth, the asymmetrical effect of lending rate on economic growth has received far less attention in the economic literature. To contribute to literature, this paper uses yearly time series data covering the period of 1970 to 2019 to study the asymmetric effect of lending rate on economic growth of Ghana. Using the nonlinear autoregressive distributed lag (NARDL) model as an estimation strategy, we found evidence of long-run and short-run asymmetrical effects of lending on economic growth of Ghana. Specifically, the estimates from long-run and short-run dynamic NARDL suggest that positive changes in lending rate generate a decrease of nearly 0.151% and 0.213% in economic growth while negative changes lead to an increase of about 0.214% and 0.677% in economic growth, respectively. Other key findings from this study also showed that the time it takes for economic growth to respond to positive changes in lending rate is different from the time it takes to respond negative changes in lending rate in the short run, providing further evidence of the presence of asymmetries inherent in lending rate. Our results are robust to different diagnostic and reliability checks. The findings from this study help us to understand that the mix outcome among studies that seeks to examine the link between lending rate and economic growth might be due to failure to account for asymmetric tendencies inherent in lending rate.
Keywords: 650; Economic growth; lending rate; NARDL and Ghana